Perubahan sifat fisis dan mekanis pelet bambu andong (Gigantochloa pseudoarundinaceae) setelah perlakuan torefaksi - Karina Gracia Agatha Tambunan; Bagus Saputra; Intan Fajar Suri; Indra Gumay Febryano; Afif Bintoro; Wahyu Hidayat (AGROINTEK, 2023)
Torrefaction has been well known to improve the properties of various biomass pellets. However, the study on torrefaction of andong bamboo pellet is still limited. This study aimed to evaluate the changes in the physical and mechanical properties of Andong bamboo (Gigantochloa pseudoarundinaceae) pellets resulting from torrefaction.  The pellets were torrefied at 200°C, 240°C, and 280°C using an electric furnace for 50 min.  The physical properties analyzed were color, moisture content, density, water adsorption, and resistance to water immersion.  A compressive strength test examined the mechanical property.  The results showed that the color of bamboo pellets torrefied at 200°C, 240°C, and 280°C were changed, showing overall color change (∆E*) values of more than 12. The lightness (L*) of the pellet remarkably decreased with the increase of torrefaction temperature. In other words, the pellet became darker with increasing temperature. The yellow/blue chromaticity (b*) was also decreased with increasing the torrefaction temperature. However, the red/green chromaticity (a*) increased at 200℃ but decreased at 240℃ and 280℃. Moisture content and pellet density decreased with increasing torrefaction temperature.  The pellets’ water adsorption decreased as the torrefaction temperatures increased at 200℃, 240℃, and 280℃.  The results also showed that the torrefied pellets were more resistant to water immersion than the control pellet as they could maintain their original form even after 24 h immersion test.  The compressive strength decreased as increasing the temperature. The torrefaction temperature affected and improved the properties of Andong bamboo pellets.